A community-based approach to sharing knowledge before, during, and after crisis events: A case study from Thailand. (January 2016) - Kaewkitipong, Laddawan; Chen, Charlie C.; Ractham, Peter
Abstract: This study adopts a structuration perspective to examine the knowledge sharing activities within local communities using social media to combat the 7-month 2011 Thai flood crisis using a qualitative case study. The crisis represented a unique situation wherein social media was used extensively during the most catastrophic flood crisis in Thailand. Data were collected from focus groups and in-depth interviews with flood victims, community leaders, NGOs, politicians, large enterprises, and Army leaders. The study divides the crisis event into three phases: pre-, during-, and post-crisis, treating each as both separate and interrelated, due to the changing information needs. The socialization and structuration theories were used as theoretical lenses to investigate how social media can play an important role in knowledge sharing activities in each phase of a crisis. The case study shows that social media can be adapted to fit the information and knowledge needs in each phase. This study's findings are useful and relevant for crisis managers, and clarify the potential usefulness of social media as a knowledge sharing tool during a crisis. Highlights: Case study analyzing 3 phases (pre, during, and post) of the 2011 Thai flood crisis. Adopts structuration and socialization theories to examine social media use during a crisis. Data collected from focus groups and interviews with numerous stakeholders. Information and knowledge needs, modes, and relations change as crises progress. Social media can be adapted to fit the information and knowledge needs in each phase.